Three‐Dimensional Image of a Baffle Leak in a Patient with a Mustard Operation. Issue 10 (18th September 2014) - Cua, Clifford L.; Kollins, Kevin; Roble, Sharon; Holzer, Ralf J.
Mini‐Abstract Baffle leaks are one type of complication following the Mustard operation for transposition of the great arteries. In this case, a 27‐year‐old male status post–Mustard operation scheduled for a pacemaker placement was noted to have a positive agitated saline contrast study via transesophageal echocardiography. The baffle leak could not be well defined despite extensive two‐dimensional imaging. With three‐dimensional imaging, the superior and posterior located baffle leak was clearly imaged. Three‐dimensional echocardiography allows unparalleled imaging in identifying the location of baffle leaks in patients with complex intracardiac procedures such as the Mustard operation.